2017
DOI: 10.7897/2230-8407.0712159
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite Profiling and in Vitro Assessment of Antimicrobial and Antioxidant Activities of Lichen Ramalina Inflata

Abstract: Lichen, a symbiotic form of fungi and algae has been known for its metabolites, but, much of the metabolites remain unexplored. It's excellent biomedical potential with active substances are being applied for medicinal purposes for the past few years. By considering the active compounds, the present study aims at reporting the anti-microbial and anti-oxidant activities of less explored lichen, Ramalina inflata. Lichen sample was collected from Kolli hills of Eastern Ghats in the range of above 1000MSL. Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 19 publications
(16 reference statements)
1
11
0
Order By: Relevance
“…Among the lichen species under the study, P. praesorediosum was found to have more antimicrobial activity than that of D. aegialita against all the pathogen tested. This finding was in line with another study that found that extracts of acetone, methanol, petroleum ether, and diethyl ether from three species of foliose lichen, Dirinaria picta, Dirinaria papillulifera, and Dirinaria applanata, had antimicrobial activity against human pathogenic bacteria and fungi using a well-diffusion method against human pathogenic bacteria and fungi [78,79]. Earlier reports also indicated that extracts of P. praesorediosum in methanol, acetone, hexane, and dichloromethane have inhibitory action against bacterial and fungal diseases [80].…”
Section: Discussionsupporting
confidence: 90%
“…Among the lichen species under the study, P. praesorediosum was found to have more antimicrobial activity than that of D. aegialita against all the pathogen tested. This finding was in line with another study that found that extracts of acetone, methanol, petroleum ether, and diethyl ether from three species of foliose lichen, Dirinaria picta, Dirinaria papillulifera, and Dirinaria applanata, had antimicrobial activity against human pathogenic bacteria and fungi using a well-diffusion method against human pathogenic bacteria and fungi [78,79]. Earlier reports also indicated that extracts of P. praesorediosum in methanol, acetone, hexane, and dichloromethane have inhibitory action against bacterial and fungal diseases [80].…”
Section: Discussionsupporting
confidence: 90%
“…The presence of phenols confirmed the antioxidant property of lichens and it is important to confirm the phenolic contents in order to justify their contribution to antioxidant activity 20 . The antioxidant property of lichens were already confirmed by several studies 21 .…”
Section: Antioxidant Activitymentioning
confidence: 62%
“…The results of ethyl acetate extract of P. tinctorum are supportive in agreement to the report given by Raj et al (2014). Ganesan et al (2017) found that methanol extract of Ramalina inflata (80μg/ml) was significantly lower than benzene extract (100 μg/ml) of those recorded in the fructicose lichen. The results of the present study are consistent with the report of Ganesan et al (2017), in that the antioxidant activity in the petroleum ether extract was lower than that of the other extracts.…”
Section: Abts + Radical Scavenging Activitymentioning
confidence: 83%
“…Ganesan et al (2017) found that methanol extract of Ramalina inflata (80μg/ml) was significantly lower than benzene extract (100 μg/ml) of those recorded in the fructicose lichen. The results of the present study are consistent with the report of Ganesan et al (2017), in that the antioxidant activity in the petroleum ether extract was lower than that of the other extracts. The results of ethanol extract of U. longissima are in accordance with the findings of Aydin et al (2018) who reported that ABTS radical scavenging assay for U. longissima ethanol extract and ethyl acetate were found as 73.31 ± 0.007% at 4000 µg/mL and 54.92 ± 0.010% at 4000 µg/ml respectively.…”
Section: Abts + Radical Scavenging Activitymentioning
confidence: 83%